Targeting Regulatory Noncoding RNAs in Human Cancer: The State of the Art in Clinical Trials - Roberto Piergentili; Stefano Sechi (Pharmaceutics)
Noncoding RNAs (ncRNAs) are a heterogeneous group of RNA molecules whose classification is mainly based on arbitrary criteria such as the molecule length, secondary structures, and cellular functions. A large fraction of these ncRNAs play a regulatory role regarding messenger RNAs (mRNAs) or other ncRNAs, creating an intracellular network of cross-interactions that allow the fine and complex regulation of gene expression. Altering the balance between these interactions may be sufficient to cause a transition from health to disease and vice versa. This leads to the possibility of intervening in these mechanisms to re-establish health in patients. The regulatory role of ncRNAs is associated with all cancer hallmarks, such as proliferation, apoptosis, invasion, metastasis, and genomic instability. Based on the function performed in carcinogenesis, ncRNAs may behave either as oncogenes or tumor suppressors. However, this distinction is not rigid; some ncRNAs can fall into both classes depending on the tissue considered or the target molecule. Furthermore, some of them are also involved in regulating the response to traditional cancer-therapeutic approaches. In general, the regulation of molecular mechanisms by ncRNAs is very complex and still largely unclear, but it has enormous potential both for the development of new therapies, especially in cases where traditional methods fail, and for their use as novel and more efficient biomarkers. Overall, this review will provide a brief overview of ncRNAs in human cancer biology, with a specific focus on describing the most recent ongoing clinical trials (CT) in which ncRNAs have been tested for their potential as therapeutic agents or evaluated as biomarkers.